1959
DOI: 10.1136/sti.35.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Female Consorts of Men with Non-gonococcal Urethritis

Abstract: cases no treatment was given to patients in whom 245 copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1964
1964
1981
1981

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Why then is there so commonly a relapse in 10 to 20% of cases, independent of the amount of tetracyclines given ? Treatment of contacts on an empirical basis is widely accepted as necessary, but this has not been validated statistically, and no evidence has appeared to support treatment of contacts (Rosedale, 1959).…”
Section: Discussionmentioning
confidence: 99%
“…Why then is there so commonly a relapse in 10 to 20% of cases, independent of the amount of tetracyclines given ? Treatment of contacts on an empirical basis is widely accepted as necessary, but this has not been validated statistically, and no evidence has appeared to support treatment of contacts (Rosedale, 1959).…”
Section: Discussionmentioning
confidence: 99%
“…In our present state of ignorance, the best that one can do is to examine the female partner when possible and attempt to treat any abnormality that may be found. It has been suggested that mere empirical treatment of the female partner serves no useful purpose (Rosedale, 1959). Also, in the author's experience, many male patients return to the same female partner after treatment of an episode of N.G.U.…”
Section: Other Sexually Transmitted Conditionsmentioning
confidence: 96%
“…The incidence of T. vaginalis in males with urethritis has been studied by a number of workers (Feo, Varano, andFetter, 1956: Symposium on Trichomonal Infestations, 1957;Lanceley, 1953Lanceley, , 1958Burgess, 1959;Rosedale, 1959;Sylvestre, Belanger, and Gallai, 1960;Willcox andRosedale, 1962, Wisdom andDunlop, 1965). From these studies it is apparent that the incidence of trichomonal urethritis in the male is variable.…”
Section: (D) Trichomonas Vaginalismentioning
confidence: 99%